2018
DOI: 10.1101/430215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Locus Suicide Recombination actively occurs on the functionally rearranged IgH allele in B-cells from inflamed human lymphoid tissues

Abstract: B-cell activation yields abundant cell death in parallel to clonal amplification and remodeling of immunoglobulin (Ig) genes by activation-induced deaminase (AID). AID promotes affinity maturation of Ig variable regions and class switch recombination (CSR) in mature B lymphocytes. In the IgH locus, these processes are under control by the 3' regulatory region (3'RR) super-enhancer, a region demonstrated in the mouse to be both transcribed and itself targeted by AID-mediated recombination. Alternatively to CSR,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The same study showed that disease‐associated SNPs occur in superenhancers of disease‐relevant cells and that this occurs more frequently in superenhancers than in typical enhancers. Recent evidence has also been provided for a role of 3′RRs in the so‐called locus suicide recombination occurring during B cells maturation (Dalloul et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The same study showed that disease‐associated SNPs occur in superenhancers of disease‐relevant cells and that this occurs more frequently in superenhancers than in typical enhancers. Recent evidence has also been provided for a role of 3′RRs in the so‐called locus suicide recombination occurring during B cells maturation (Dalloul et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…1B). LSR targeted the two 3'RRs, occurred at low frequency in healthy individuals, and was AID-dependent as judged by the absence of LSR in AID-deficient patients (Dalloul et al, 2019).…”
Section: The 3'rr and Locus Suicide Recombinationmentioning
confidence: 98%
“…LSR reportedly occurred at levels approaching classical CSR as detected by PCR/Southern blot on excised episomal circles (Péron et al, 2012), though apparently not by more sensitive techniques (Meng et al, 2014;Qian et al, 2014). Recently, LSR was also detected at the human IgH locus undergoing CSR, suggesting conservation of the process between humans and mice (Dalloul et al, 2019). The human IgH locus contains two 3'RRs that include switch-like repeats:…”
Section: The 3'rr and Locus Suicide Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…LSR results in the complete deletion of the cluster of IgH constant genes. When LSR hits the active IgH locus, it induces the loss of BCR expression and the death of the B-cell [9][10][11] .…”
Section: • Introductionmentioning
confidence: 99%